Sinergie Percorsi interistituzionali per la riqualificazione delle aree militari - Fiorino, Donatella Rita (CONDIVISIONI. Studi e ricerche sul patrimonio difensivo e militare, 2022)
This volume illustrates the research, teaching and third mission experiences undertaken by the University of Cagliari in the field of preservation, redevelopment and enhancement of historic military heritage with particular regard to the activities carried out within the institutional framework of the collaboration agreement signed with the Ministry of Defense in 2018. The studies, conducted on a wide and heterogeneous heritage, introduce and exemplify some of the many strands of research that the series intends to accommodate, opening towards interdisciplinary comparison and collaboration with other scientific communities involved nationally in similar research contexts.